To film an inconceivable reality: the manifesto of the young Kieślowski - Mikołaj Jazdon (Images)
In his master’s thesis, Documentary Film and Reality, Krzysztof Kieślowski dealt with a number of problems that turned out to play a vital role in his future film career, and its documentary period in particular. This range of topics includes the concept of ‘the dramaturgy of reality’, one of the methods for factual filmmaking he intended to put into practice, but also such ideas as the relation between film and literature, between documentary film and ethics, and the difference between reportage and documentary filmmaking. These concepts had an influence on his documentary filmmaking and led him to develop other concepts and methods for documentary filmmaking. From the perspective of Kieślowski’s creative oeuvre, the thesis Documentary Film and Reality reads as a manifesto by the young filmmaker.